Between evidence-based education and analysis of teaching practices. A review of didactic research on the Italian high school system - Giuseppe Tacconi (Firenze University Press, 2015)
The document proposes a review of the didactic research on higher education which, in recent years, has been conducted in Italy, referring also to the international research landscape. This is an evidence-based education research, but also a research based on the so-called branches of the analysis of teaching practices and routines. It draws an overview highlighting the specificity of the various branches and emphasizing the possibility to combine them profitably.